PENGARUH TENAGA KERJA DAN INVESTASI TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI SUMATERA SELATAN PERIODE TAHUN 2001-2020: PENGARUH TENAGA KERJA DAN INVESTASI TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI SUMATERA SELATAN PERIODE TAHUN 2001-2020 (Ekonomika, 2022)
This study title of this research is The Influence of Labor and Investment on Economic Growth in South Sumatra Province for the Period of 2001-2020. The purpose of this study is to determine the influence of Labor and Investment on Economic Growth in South Sumatra Province. This study uses time series data from 2001-2020 using multiple linear regression analysis techniques with the Ordinary Least Square (OLS) method. The findings of this study indicate that partially the labor has a significant positive influence on economic growth in South Sumatra Province while investment has a negative but insignificant influence on economic growth in South Sumatra Province. Simultaneously, Labor and investment have a significant influence on economic growth in South Sumatra Province with a coefficient of determination (R2) of 0.961, which means that the contribution that can be given by the Labor and Investment variables to economic growth in South Sumatra Province is 96.1 percent while the remaining 3.9 percent is explained by other variables not included in this study.